(untitled) (Scientific journal of the Fergana State University, 2024)
The regional specificity of people’s life creates conditions for the development of each people’s culture and makes it possible to name objects and concepts. In this way, a brand name is formed, it affects the social mentality of people, and the practical direction of national brands is revealed. In this article, the importance of the linguistic and cultural research of the nomination of brands, their different semantic aspects, and the fact that the meaning-content-characteristic features of independently named concepts are in many cases made up of language units with national-cultural content. Of course, national-mental phenomena play an important role in naming brands. It is understood that it is possible to get information about Uzbek national culture, values, especially national traditions through Uzbek national brands.